2019
DOI: 10.1186/s13037-019-0215-3
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary reaming modality for management of postoperative long bone infection: a prospective randomized controlled trial in 44 patients

Abstract: BackgroundStudies addressing the management of intramedullary infection are mainly retrospective and with a limited number of cases. Reaming can be performed using either conventional reaming or using the reamer/irrigator/aspirator (RIA) system. Until now there have been no comparative prospective studies between these two methods. We aimed to compare the efficacy of RIA with conventional reaming followed by insertion of antibiotic-loaded cement, for the treatment of intramedullary nail infection of long bones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The baseline characteristics of the patients included in the study demonstrated a predominance of male patients with a mean age of 39.76 years. This is consistent with previous studies that have reported a higher incidence of these types of fractures in male patients and that these injuries tend to occur in younger patients [ 8 , 9 ]. In terms of fracture grade, 46.7% of the patients had GA grade 3 fractures, indicating a more severe type of injury.…”
Section: Discussionsupporting
confidence: 93%
“…The baseline characteristics of the patients included in the study demonstrated a predominance of male patients with a mean age of 39.76 years. This is consistent with previous studies that have reported a higher incidence of these types of fractures in male patients and that these injuries tend to occur in younger patients [ 8 , 9 ]. In terms of fracture grade, 46.7% of the patients had GA grade 3 fractures, indicating a more severe type of injury.…”
Section: Discussionsupporting
confidence: 93%
“…Another treatment option with recently reported good results for medullar cavity reaming and lavage is the combined use of the reamer-irrigator-aspirator (RIA) system and antibiotic-coated nails (Kanakaris et al, 2014;Finelli et al, 2019). By using the RIA system, surgeons do not need to create a bone window, and, therefore, the procedure morbidity is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Although a limited number of studies investigated the efficacy of the RIA‐system for the treatment of long bone FRI, 10,15,16 our study is, to the best of our knowledge, the first to compare standard tissue cultures to cultures obtained using the RIA‐system for the diagnosis of FRI. A recent randomized controlled trial compared the RIA‐system to standard intramedullary reaming for the treatment of FRI 16 . Although tissue cultures retrieved by the RIA‐system were included as a diagnostic modality in that study, no comparison was made between sampling methods.…”
Section: Discussionmentioning
confidence: 99%